2022
DOI: 10.1111/imig.13100
|View full text |Cite
|
Sign up to set email alerts
|

The Ukrainian refugee crisis: Unpacking the politics of pet exceptionalism

Abstract: The rescue of pets soon became part of the humanitarian narrative of the attack on Ukraine. The open‐door policy on companion animals from Ukraine—a high‐risk country for rabies—in terms of regulatory modifications and the provision of services could be described as one of ‘pet exceptionalism’. While the influx of pets and the response to it has significance for the international refugee regime, there has been scant scholarly engagement with the movement of pets across borders during emergencies. To bridge aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Additionally, Napp et al (2010) showed that by implementing stricter controls, there was a 270-fold decrease in disease risk. This highlights the Sandvik, 2022;Silverwood, 2022b). In order to better understand the risk via this scheme, future research should focus on surveying official veterinarians on the guidance issued as well as questioning Ukrainian refugees on the information they received and their levels of compliance with the guidance.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, Napp et al (2010) showed that by implementing stricter controls, there was a 270-fold decrease in disease risk. This highlights the Sandvik, 2022;Silverwood, 2022b). In order to better understand the risk via this scheme, future research should focus on surveying official veterinarians on the guidance issued as well as questioning Ukrainian refugees on the information they received and their levels of compliance with the guidance.…”
Section: Discussionmentioning
confidence: 86%
“…On 24 February 2022, Ukraine was invaded by Russian troops, leading to the ongoing conflict in the country. To date, nearly 5 million refugees have fled to the EU from Ukraine (UNHCR, 2023) with many bringing their pets with them (Sandvik, 2022). In response to this crisis, the European Commission (EC), on 25 February 2022, declared a relaxation to the rules on importation under the Article 32 derogation within Regulation (EU) No.…”
Section: Introductionmentioning
confidence: 99%
“…At present, Norway, and Europe more broadly, may be seen as a de-escalated chaotic geography. By activating the temporary protection directive for Ukrainian refugees, the region has proactively used regulatory tools to de-escalate an ongoing emergency (Sandvik, 2022). Chaos has not ensued.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, across Europe and North America, the warm welcome to a white European, Christian population, consisting predominantly of women (53%) and children (32%) (DLUHC 2023), contrasts starkly with entrenched racialised Fortress Europe bordering practices and "stop the boats" kinds of discourses (Hyndman 2023;Moise et al 2024). Even Ukrainian pets are being accommodated within usually draconian and Kafkaesque European bio-bordering and visa regimes (Sandvik 2023). This adds a new iteration to the real and discursive filtering of "foreigners" employed through domopolitics (Gunaratnam 2021;Walters 2004).…”
Section: Introduction: the Uk's Homes For Ukraine Schemementioning
confidence: 99%
“…2024). Even Ukrainian pets are being accommodated within usually draconian and Kafkaesque European bio‐bordering and visa regimes (Sandvik 2023). This adds a new iteration to the real and discursive filtering of “foreigners” employed through domopolitics (Gunaratnam 2021; Walters 2004).…”
Section: Introduction: the Uk's Homes For Ukraine Schemementioning
confidence: 99%